Inhibition of Pseudomonas aeruginosa secreted virulence factors reduces lung inflammation in CF mice. Issue 1 (31st December 2018) - Sandri, Angela; Ortombina, Alessia; Boschi, Federico; Cremonini, Eleonora; Boaretti, Marzia; Sorio, Claudio; Melotti, Paola; Bergamini, Gabriella; Lleo, Maria
ABSTRACT: Background : Cystic fibrosis (CF) lung infection is a complex condition where opportunistic pathogens and defective immune system cooperate in developing a constant cycle of infection and inflammation. The major pathogen, Pseudomonas aeruginosa, secretes a multitude of virulence factors involved in host immune response and lung tissue damage. In this study, we examined the possible anti-inflammatory effects of molecules inhibiting P. aeruginosa virulence factors. Methods : Pyocyanin, pyoverdine and proteases were measured in bacterial culture supernatant from different P. aeruginosa strains. Inhibition of virulence factors by sub-inhibitory concentrations of clarithromycin and by protease inhibitors was evaluated. Lung inflammatory response was monitored by in vivo bioluminescence imaging in wild-type and CFTR-knockout mice expressing a luciferase gene under the control of a bovine IL-8 promoter. Results : The amount of proteases, pyocyanin and pyoverdine secreted by P. aeruginosa strains was reduced after growth in the presence of a sub-inhibitory dose of clarithromycin. Intratracheal challenge with culture supernatant containing bacteria-released products induced a strong IL-8-mediated response in mouse lungs while lack of virulence factors corresponded to a reduction in bioluminescence emission. Particularly, sole inactivation of proteases by inhibitors Ilomastat and Marimastat also resulted in decreased lung inflammation. Conclusions : Our data support the assumption that virulence factors are involved in P. aeruginosa pro-inflammatory action in CF lungs; particularly, proteases seem to play an important role. Inhibition of virulence factors production and activity resulted in decreased lung inflammation; thus, clarithromycin and protease inhibitors potentially represent additional therapeutic therapies for P. aeruginosa -infected patients.